Obtenção e purificação de L-asparaginase de Zymomonas mobilis produzida por Escherichia colirecombinante - Gonçalves, Vinícius de Lima (2019)
The acute lymphoblastic leukemia (ALL) is a cancer of the lymphatic system with an important incidence, especially, in child population. The enzyme L-asparaginase has a recognized effectiveness in the therapy of this cancer. The Brazil does not have a way to produce the enzyme to clinical use. Currently, patients with the disease depend on the importation of the medicine to continue the treatment. Finding a national way of producing L-asparaginase is of vital importance in improving the viability and efficiency of ALL treatment. In this scenario, the present work studiesthe extraction and purification conditions of the enzyme encoded by the recombinantly expressed Zymomonas mobilis bacterial gene in Escherichia coli. The cell rupture by high-pressure homogenization and two steps chromatography purification were studied. It was determined that the best cell rupture conditions are 300 bar and 4 passages. The first chromatography step was by immobilized ion affinity chromatography and presented a 12,1 purification factor with 88% recovery. The second step was by ion exchange chromatography, which obtained 3,5 recuperation factor and 69,5% recovery. The purity degree obtained makes possible the animal studies of this national enzyme and start the studies for a process escalation.